Outcomes of post‐prostatectomy radiotherapy at a Regional Cancer Centre. Issue 4 (14th August 2017) - Nicholls, Luke; Winter, Amber; Harwood, Ashley; Plank, Ashley; Bagga, Preeti; Wong, Winnie; Khoo, Eric
Abstract: Introduction: To investigate the efficacy and toxicity of radiation therapy (RT) after radical prostatectomy (RP) for prostate cancer at Radiation Oncology Centres, Toowoomba. Methods: The electronic medical records of 130 consecutive patients with histologically proven prostate adenocarcinoma who underwent post‐prostatectomy RT between January 2008 and December 2014 were analysed. Primary endpoint was Biochemical Recurrence (BCR) after RT. BCR was defined by PSA > 0.2 ng/mL and BCR endpoints were analysed using Kaplan–Meier methods. The impact of RT technique and the rates of acute and late toxicities are also reported. Toxicities were graded according to Radiation Therapy Oncology Group (RTOG) criteria. Results: Median follow‐up time after RT (regardless of technique) was 28 months. BCR occurred in 32 of the 126 patients (25%) whose prostate specific antigen (PSA) levels have been monitored post‐RT. At 24 and 36 months, 85% and 75% of patients were BCR‐free, respectively. Patients with a pre‐RT PSA above 0.2 ng/mL had a higher probability of recurrence than patients with values below 0.2 ng/mL ( P  =   0.03). RT technique, pelvic nodal irradiation, androgen deprivation therapy, T staging or surgical margin did not significantly impact BCR results. No patient experienced acute toxicities greater than grade 2. Grade 1 or 2 late gastrointestinal (GI) toxicity occurred in 11% and 1 patient experienced a grade 3 event. 12% of patients developed grade 1 or 2 late genitourinary (GU) toxicity, with evidence of grade 3 severity in only 1 patient. Evidence of a trend in reduction in late GI toxicity with the use of intensity modulated radiation therapy (IMRT) or volumetric modulated arc therapy (VMAT) was apparent but not with late GU toxicity. Conclusion: At our regional centre, early RT (PSA < 0.2 ng/mL) was associated with significant improvement in BCR‐free survival. Rates of toxicity mirror those of landmark trials which suggest no detriment for our regional prostate cancer patients. The use of IMRT/VMAT techniques was associated with a trend towards reduced rates of GI toxicity. Abstract : This study investigated the outcomes of 130 patients treated with adjuvant or salvage radiation therapy following radical prostatectomy for prostate adenocarcinoma. In our regional centre, early RT (PSA < 0.2 ng/mL) was associated with significant improvement in recurrence‐free survival. Rates of toxicity mirror those of landmark trials which suggest no detriment for our regional prostate cancer patients.